2019
DOI: 10.1161/strokeaha.119.026221
|View full text |Cite
|
Sign up to set email alerts
|

Educating Paramedics on the Finger-to-Nose Test Improves Recognition of Posterior Stroke

Abstract: Background and Purpose— Emergency medical services (EMS) stroke recognition facilitates rapid care, however, prehospital stroke screening tools rely on signs that are often absent in posterior circulation strokes. We hypothesized that addition of the finger-to-nose (FTN) test to the Cincinnati Prehospital Stroke Scale would improve EMS posterior stroke recognition. Methods— In this controlled before and after study of consecutive EMS transported posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Compared with the ABCD2 score, our nomogram model yielded a better diagnostic performance with higher AUC value. We hypothesize that the inclusion of the finger to nose and tandem gait tests might partly account for high accuracy of our model to a certain extent since both are reportedly powerful predictors for posterior circulation ischemia and minor stroke (35,40,41). In comparison, ABCD2 score was initially generated to assess the risk of early stroke after a transient ischemic attack and incorporate signs of anterior circulation abnormal and features of medical history (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the ABCD2 score, our nomogram model yielded a better diagnostic performance with higher AUC value. We hypothesize that the inclusion of the finger to nose and tandem gait tests might partly account for high accuracy of our model to a certain extent since both are reportedly powerful predictors for posterior circulation ischemia and minor stroke (35,40,41). In comparison, ABCD2 score was initially generated to assess the risk of early stroke after a transient ischemic attack and incorporate signs of anterior circulation abnormal and features of medical history (61).…”
Section: Discussionmentioning
confidence: 99%
“…We searched for predictors of stroke from keynote papers (3,31,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Candidate predictors were identified when the factors were consistently reported in predictive research on patients with dizziness, easily ascertained, and routine diagnostic tests for patients with stroke.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…One ambulance service in the UK added nausea to their prehospital stroke screening tool, which also includes vertigo, visual problems, and ataxia as further signs indicative of PCS (88). Another study demonstrated that an initiative as simple as training paramedics to perform the finger-to-nose test may facilitate PCS identification (89). The particular relevance of such efforts is also emphasized in the context of a recent study suggesting that ED staff does appear to rely on EMS staff 's diagnostic impression (31).…”
Section: Approaches To Solving the Problem Of Psc Misdiagnosis Improving Symptom Recognition Prehospitally And During Triagementioning
confidence: 99%
“…Training of EMS to better use these tools is a possible avenue to improve screening, as is the creation of a tool that balances ease of use with high sensitivity and specificity and that ensures high interrater reliability and ease of use for inter-linguistic communication. Moreover, these tools are poor in identifying posterior circulation stroke patients [49].…”
Section: Ems Use Of Stroke Screening Toolsmentioning
confidence: 99%
“…One study reported a median onset to door time of 60 min longer compared to anterior circulation stroke patients [51]. They are often not identified as the most common symptoms including eye deviation, visual disturbance and dizziness [52] are not accounted for in many stroke screening tools [49]. It has been noted that the basic FAST (Face, Arm, Speech and Time) screen missed 40% of PCS [53], however, if vertigo, ataxia and visual symptoms were added only 8% of PCS were missed [53].…”
Section: Posterior Circulation Strokesmentioning
confidence: 99%